Biochemical and Nutritional Profiles in Asthma Patients with Perceived Food Allergies: A Hospital-Based Case-Control Study in India - Dadha, Priyanka; Nallagatla, Himaja (Journal of Asian Health, 2024)
Objective: The current study explored the biochemical and dietary profile of asthma patients with and without perceived food allergy (FA). Methods: A case-controlled study was conducted with 286 patients (143 asthmatics with perceived food allergy and 143 age, sex, SES matched asthmatics with no perceived food allergy) aged 15-40 years. The blood sample was collected, and Food Frequency Questionnaire was recorded for laboratory investigations and nutrients calculation respectively. Relevant biochemical parameters (complete blood picture, total serum IgE etc.) were analyzed in the blood samples and macro and micronutrients (calories, protein, fat, Vit-B complex, Calcium etc.) were calculated and comparisons were made between the cases and controls. Results: Most of the cases had higher BMI (27.5±4.82) than controls (23.3±4.51) (p≤0.05); 59(41.3%) and 46(32.2%) had BMI in the range of 25-30 and >30. The perceived food allergy in asthmatics was associated with biochemical parameters (Hb, TLC, Eosinophil counts, Monocytes, Serum IgE, Serum protein and serum calcium) and nutrients[protein(42.24±7.63g/d), fat(23.86±4.70g/d), thiamine(0.77±0.15mg/d), riboflavin(1.20±0.19mg/d), pyridoxine(1.53±0.16mg/d), folic acid(70.80±8.69µg/d), cobalamine(0.70±0.03 mg/d), ascorbicacid(34.51±4.26mg/d), calcium(304.10±62.36 mg/d), and iron(17.94±4.97 mg/d)] as compared to their counterparts with no perceived food allergy(p≤0.05). Conclusion: Asthmatics eliminate food items based on self-perception which may lead to nutrients deficiency and abnormal blood reports. There is a need to confirm FA diagnosis and develop appropriate framework to manage FA in asthmatics. More studies are needed to estimate association of asthma and food allergy with micronutrient deficiency and Body Mass Index. Key words: asthma, food allergy, laboratory investigations, nutrients intake, body mass index